Evaluation of homelessness services to adults in the secure estate : Executive Summary.: Executive Summary. Social Research Number: 37/2018 (2018) - Madoc-Jones, I; Hughes, C; Dubberley, S; Gorden, C (Caro); Washington-Dyer, K (Karen); Wilson, F; Ahmed, A; Lockwood, K; Wilding, M
No abstract available